2019
DOI: 10.1016/j.aquaculture.2019.01.059
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the digestive enzyme activity of the Amazonian pimelodid catfish Pseudoplatystoma punctifer (Castelnau, 1855)

Abstract: Highlights ► The ontogeny of the digestive enzymes activity was studied in Pseudoplatystoma punctifer, a tropical catfish species with high aquaculture potential in Amazonia. ► P. punctifer showed a fast digestive system development with an enzymatic profile typical of a tropical and carnivorous species. ► Results revealed that the digestive system of P. punctifer was fully functional at 12 days post fertilization, indicating that this species could be weaned from that day onwards. ► Results contribute to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 56 publications
7
29
1
10
Order By: Relevance
“…Thereafter, specific lipase activity dramatically increased at 15 dph, but then sharply decreased until end of the study. Similar pattern has been documented in Lates calcarifer [3] , Clarias magur [8] , Odontesthes bonariensis [25] , Pseudoplatystoma punctifer [44] , Mystus nemurus [45] . The total lipase activity was also detected at hatching at near zero and remained the low levels until 10 dph.…”
Section: Discussionsupporting
confidence: 80%
“…Thereafter, specific lipase activity dramatically increased at 15 dph, but then sharply decreased until end of the study. Similar pattern has been documented in Lates calcarifer [3] , Clarias magur [8] , Odontesthes bonariensis [25] , Pseudoplatystoma punctifer [44] , Mystus nemurus [45] . The total lipase activity was also detected at hatching at near zero and remained the low levels until 10 dph.…”
Section: Discussionsupporting
confidence: 80%
“…The feeding protocol used in this study was adapted to the digestive capacities of developing P. punctifer . Thus, individuals were weaned at 13 dpf from live prey ( Artemia nauplii) to the different experimental compound diets when the morphological and functional development of the digestive system was achieved [ 23 , 24 ], moment that we consider, from a digestive physiology point of view, the beginning of the juvenile stage in this species.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the pancreatic and intestinal enzymes are useful and reliable markers for assessing the development and state of the digestive function in fish [ 80 ]. As in many other fish, the specific activity of AP increases concomitantly with the decrease in the activity of LAP during the larval development of P. punctifer [ 24 ]. In this study, the ratio AP/LAP at 26 dpf measured in the four dietary groups indicated a lower degree of maturation of the intestine in the 30:10 and 30:15 groups, whereas the most mature intestine corresponded to individuals from the 45:15 group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations